Average Weight of Seminal Vesicles: An Adjustment Factor for Radical Prostatectomy Specimens Weighed With Seminal Vesicles. (December 2015) - Tjionas, George A.; Epstein, Jonathan I.; Williamson, Sean R.; Diaz, Mireya; Menon, Mani; Peabody, James O.; Gupta, Nilesh S.; Parekh, Dipen J.; Cote, Richard J.; Jorda, Merce; Kryvenko, Oleksandr N.
The International Society of Urological Pathology in 2010 recommended weighing prostates without seminal vesicles (SV) to include only prostate weight in prostate-specific antigen (PSA) density (PSAD) calculation, because SV do not produce PSA. Large retrospective cohorts exist with combined weight recorded that needs to be modified for retrospective analysis. Weights of prostates and SV were separately recorded in 172 consecutive prostatectomies. The average weight of SV and proportion of prostate weight from combined weight were calculated. The adjustment factors were then validated on databases of 2 other institutions. The average weight of bilateral SV was 6.4 g (range = 1-17.3 g). The prostate constituted on average 87% (range = 66% to 98%) of the total specimen weight. There was no correlation between patient age and prostate weight with SV weight. The best performing correction method was to subtract 6.4 g from total radical prostatectomy weight and to use this weight for PSAD calculation. The average weights of retrospective specimens weighed with SV were not significantly different between the 3 institutions. Using our data allowed calibration of the weights and PSAD between the cohorts weighed with and without SV. Thus, prostate weight in specimens including SV weight can be adjusted by subtracting 6.4 g, resulting in significant change of PSAD. Some institution-specific variations may exist, which could further increase the precision of retrospective analysis involving prostate weight and PSAD. However, unless institution-specific adjustment parameters are developed, we recommend that this correction factor be used for retrospective cohorts or in institutions where combined weight is still recorded.